Development of a Sequence Searchable Database of Celiac Disease-Associated Peptides and Proteins for Risk Assessment of Novel Food Proteins - Amnuaycheewa, Plaimein; Abdelmoteleb, Mohamed; Wise, John; Bohle, Barbara; Ferreira, Fatima; Tetteh, Afua O.; Taylor, Steve L.; Goodman, Richard E. (Frontiers in Allergy, 2022)
Celiac disease (CeD) is an autoimmune enteropathy induced by prolamin and glutelin proteins in wheat, barley, rye, and triticale recognized by genetically restricted major histocompatibility (MHC) receptors. CeD patients must avoid consuming these proteins. Regulators in Europe and the United States expect an evaluation of CeD risks from proteins in Genetically Modified (GM) crops or novel foods for wheat related proteins. Our database includes evidence-based causative peptides and proteins and two amino acid sequence comparison tools for CeD risk assessment. Sequence entries are based on review of published studies of specific gluten-reactive T cell activation or intestinal epithelial toxicity. The initial database in 2012 was updated in 2018. The current database holds 1,013 causative peptides and 72 representative proteins. The FASTA sequence comparison to 72 representative CeD proteins provides insurance for possible unreported epitopes. Validation was conducted using protein homologues from Pooideae and non-Pooideae monocots, dicots, and non-plant proteins. Criteria for minimum percent identity and maximum E-scores are guidelines. Exact matches to any of the 1,013 peptides suggests risks, while FASTA alignment to the 72 CeD proteins suggests possible risks. Matched proteins should be tested further by CeD specific CD4/8+ T-cell assays or in vivo challenges before use in foods.